Effect of the curvature angle in a conduit with an adiabatic cylinder over a backward facing step on the magnetohydrodynamic behaviour in the presence of a nanofluid - Derbal, Djamila (Strojniški vestnik, 2023)
A backward facing duct are present in various industrial applications especially those focused on heat transfer. The flow through a curved backward facing duct especially in the presence of nanofluid presents complexities compared to a straight backward facing step (BFS) duct. Therefore, the present numerical study deals a nanofluid flow (Fe3O4-H2O) forced convection in a curved backward facing duct. The objective of this investigation is to visualize at different curvature angles g (0°, 30°, 45°, 60°, 90°) imposed on the top wall of the duct, the effect of Hartmann number Ha (0, 50, 100), magnetic field inclination angle ? (0°, 60°, 90°), Reynolds number Re (10, 100, 200) and nanoparticle volume fraction ? (0 %, 0.05 %, 0.1 %). The dimensionless governing equations are solved using the multigrid finite element method. The results showed that the heat transfer was enhanced at the curved angle g = 90° for large Hartman numbers, thus, the average Nusselt number increased with a ratio of 240.74 % in the case of Hartmann number (Ha = 100).
Keywords: backward-facing step; curved conduit; ferrofluid; finite element method; fixed cylinder; forced convection; magnetohidrodinamika; magnetohydrodynamic; metoda končnih elementov; nazaj obrnjen korak; nepremični valj; prisilna konvekcija; ukrivljen kanal